Identification of the optimal substrate for sexual propagation of Cinchona officinalis l.: Implications for conservation and sustainable use - Marcelo Bazán, Fátima Elizabeth; Mantilla Chávez, Walter; Paredes Pajares, Katia Patricia; Chávez Cercado, Deisy Medaly; Baselly Villanueva, Juan Rodrigo; Álvarez Álvarez, Pedro (Springer, 2025)
Cinchona officinalis L., a tree species of medicinal, ecological and economic importance, inhabits one of the richest and most fragile ecosystems in the world (montane forests) where it contributes to water and climate regulation, erosion control and carbon sequestration. However, the species is subject to strong anthropogenic pressure and is currently endangered. Unfortunately, little is known about propagation and repopulation techniques or the substrate preferences of the species. We designed a randomised trial with four replications in which 12 trial substrates (peat mixed with sand, moss or pine sawdust and supplemented with chicken manure, guano, compost or agricultural soil) were evaluated to identify the optimal substrate for the sexual propagation of Cinchona officinalis seedlings. The physical and chemical properties of the substrates were analysed, and the impact of these on the emergence, biometry and quality of seedlings were evaluated. Statistical analysis was performed using Scott-Knott and Kruskal-Wallis tests (p<0.05), principal component analysis, heatmap analysis and correlation analysis. The substrate composed of peat, moss and agricultural soil (ratio, 2:2:0.5) was found to be optimal, consistently producing the highest emergence rates and superior biometrics and quality indices. These findings represent a remarkable advance in the propagation of C. officinalis and provide valuable insights enabling the vulnerability of this species to be addressed in ecosystems subject to anthropogenic pressures, thus ensuring the conservation and sustainable use of the species.